Numerical simulation of sub-gap defect states and electron transport mechanisms in amorphous Si–Zn–Sn–O thin film transistors. (1st November 2022) - Saha, D.; Lee, Sang Yeol
Abstract: Thin film transistors (TFTs) have been fabricated using room temperature radio frequency sputtered amorphous Si–Zn–Sn–O semiconductor deposited on SiO2 /Si substrates. Sub-band gap density of states (DOS) of the amorphous channel layer grown with different process oxygen flow has been investigated by 2D numerical simulation of the transfer and output curves. The extracted DOS is found to be composed of localized band tails, Gaussian shallow donors and deep level acceptor-like trap states. The overall electrical performance of the TFTs is found to be critically dependent on the sub-gap localized DOS. In addition, the positive shift in threshold voltage and decrease in field effect mobility with increasing process oxygen flow have been well explained by considering the change in shallow donor and deep acceptor states density. Numerical simulation clearly shows the formation of degenerate accumulation layer at the Si–Zn–Sn–O/SiO2 interface at higher gate voltages (VGS ≥ 16 V) which possibly results in a crossover of electron transport mechanism from trap-limited activation to percolation conduction. Such studies are crucial to explore the underlying device physics of indium free amorphous Si–Zn–Sn–O based TFTs and further improvement of device performance and stability.